Cyto-Morphological, Biochemical and Radiological Correlation of Various Thyroid Lesions at a Tertiary Care Center - Chittawadagi, Bharati Bhushan; Karthikeyan, T.M; Rajeshwari, M (Annals of Pathology and Laboratory Medicine, 2018)
Background: Fine needle aspiration cytology (FNAC) is a cost-effective and time saving diagnostic test used to specifically distinguish between benign and malignant lesions by cytology. Aim: To evaluate the cytomorphological pattern, thyroid hormone profile and radiological findings in early detection of various thyroid diseases. Objective: To correlate the findings of FNAC, thyroid hormone profile and radiological features in diagnosis of various thyroid lesions Methods: 100 patients with thyroid swellings underwent FNAC along with complete thyroid hormone profile& USG Thyroid. Result: 93 female and 7 male patients were evaluated. Mean age of patients was 38.62Â±14.2. Ninety-four patients had non-neoplastic and 6 had neoplastic lesions. Colloid goiter was the predominant group among non-neoplastic lesions, followed by Hashimotoâ€™s thyroiditis whereas follicular neoplasm was seen more frequently among neoplastic group. Majority of patients (71%) were in euthyroid state, followed by hypothyroid state and least in hyperthyroid state. In our study 88% of benign lesions were hyper-echoic and all malignant lesions were hypo-echoic. Most of the cystic nodules were benign and showed macro-calcification whereas all malignant lesions showed micro-calcification. Most of the benign lesions showed peripheral hypervascularisation and all malignant lesions showed internal hypervascularisation. There was a statistically positive significant correlation between FNAC findings and radiological features with P<0.001. Conclusion: FNAC and radiological examination play significant role in an accurate diagnosis of neoplastic and non-neoplastic lesions of thyroid gland. Thyroid profile also plays a very important role in sub-typing of non-neoplastic lesions.